2013
DOI: 10.3126/nepjoph.v5i2.8746
|View full text |Cite
|
Sign up to set email alerts
|

Central Retinal Arterial Occlusion (CRAO) after Phacoemulsification-A Rare Complication

Abstract: Background: While peribulbar anesthesia is generally safe, a remote risk of retinal vascular accident exists and its routine use should be done with caution. Objective: To report a case of central retinal artery occlusion (CRAO) that occurred within 24 hours of routine uneventful phacoemulsification cataract surgery using peribulbar anesthesia. We share our experience of a 45-year old man who underwent uneventful clear corneal temporal incision phacoemulsification cataract surgery using peribulbar lignocain in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 4 publications
1
7
0
Order By: Relevance
“…The ischemic events described in this study were noted in different hospitals with different surgeons administering the block, suggesting that this is not related to technique or idiosyncrasies in block composition. There have been reports of epinephrine-associated vasoconstriction resulting in similar findings, 6 , 7 but none of the block components in our series contained epinephrine. In a study of postvitrectomy optic neuropathy, 71% of patients experienced intraoperative hypotension, which was hypothesized to result in a drop in intraocular perfusion pressure; 8 in our cases, no intraoperative drop in systemic blood pressure was documented.…”
Section: Discussionsupporting
confidence: 72%
“…The ischemic events described in this study were noted in different hospitals with different surgeons administering the block, suggesting that this is not related to technique or idiosyncrasies in block composition. There have been reports of epinephrine-associated vasoconstriction resulting in similar findings, 6 , 7 but none of the block components in our series contained epinephrine. In a study of postvitrectomy optic neuropathy, 71% of patients experienced intraoperative hypotension, which was hypothesized to result in a drop in intraocular perfusion pressure; 8 in our cases, no intraoperative drop in systemic blood pressure was documented.…”
Section: Discussionsupporting
confidence: 72%
“…CRAO is a known but very rare complication of ocular surgery that can occur after retrobulbar, peribulbar, or sub-Tenon's anesthesia. 1 , 3 , 4 , 5 , 6 , 8 , 9 , 10 , 11 , 12 , 14 , 17 , 18 , 19 , 20 , 21 Calenda et al 4 reported CRAO after peribulbar anesthesia for PPV for RRD repair, and Jung et al 10 reported two cases of CRAO after PPV using retrobulbar anesthesia. Ascaso 1 reported transient CRAO after peribulbar anesthesia for PPV.…”
Section: Discussionmentioning
confidence: 99%
“…Central retinal artery occlusion (CRAO) is known to be a rare complication associated with ocular surgery. 11 Retrobulbar anesthetic injections are a known association, 3 , 8 , 10 , 14 , 18 , 19 , 20 though there are also reports of CRAO occurring after peribulbar 1 , 4 , 9 , 12 , 17 , 21 and sub-Tenon's 5 , 6 injections. Visual recovery is generally poor in these patients.…”
Section: Introductionmentioning
confidence: 99%
“…Central retinal artery occlusion (CRAO) has been reported as a rare complication associated to intraocular surgery in different types of ophthalmic surgery [1][2][3][4]. CRAO associated to anesthesia administration has been reported after sub-tenon [5,6], peribulbar [7][8][9][10][11] and especially retrobulbar injection [2,[12][13][14][15][16]. Visual recovery is consistently reported to be poor in these patients.…”
Section: Introductionmentioning
confidence: 99%